The effectiveness and clinical outcomes of the Minerva cervical thoracic jacket in patients with type II odontoid fractures - Ozturk, Sait; Erol, Fatih Serhat; Akgun, Bekir; Kaplan, Metin (Tubitak Scientific & Technological Research Council Turkey, 2017)
Background/aim: The objective of this study was to carry out a detailed analysis and assess the outcomes for the Minerva cervical thoracic jacket (CTJ) in patients with type II odontoid fractures who could not be surgically treated. Materials and methods: Twenty-six patients for whom the Minerva CTJ was used rather than surgery for different reasons were included in the study. All patients were fitted with the Minerva CTJ within the first 24 h following diagnosis. The patients were followed 4 weeks after hospital discharge and then at 2-week intervals. Results were considered significant at P < 0.05 and a 95% confidence interval was calculated. Results: Of the 26 patients, 17 were male and 9 were female. The mean age was 49.03 years old (range: 16-86 years old). Fusion occurred in 25 of the 26 patients (P = 0.004), and the mean time to fusion was 6.8 weeks (P = 0.002). The mean length of hospital stay was 4 days and the mean follow-up period was 7.3 weeks. None of the patients had any complications due to the Minerva CTJ and the mortality rate was 0%. Conclusions: The Minerva CTJ application was a safe and cheap technique in the management of type II odontoid fractures. It had a high fusion rate and no complications.
Keywords: Odontoid; Minerva jacket; halo; fracture; fusion; type II